Repositioning on the roads: How Automotive Brands’ current customers are reacting to Rebranding Towards Electric Vehicles - Sjunnesson,Liam; Gamal Abbas Helmy Elsayed,Mohamed; Hemmatkhah,Gillian (LBMG Strategic Brand Management - Masters Paper Series, 2025)
Purpose: The purpose of this study is to critically investigate how automotive companies reposition in relation to electrification on the market, and how the different types of repositioning affect the current customers. Methodology: This research paper uses a qualitative case study approach to explore how Jaguar, Kia, and BMW reposition their brand identities in response to electrification. Secondary data from corporate reports, industry analyses, and media sources form the basis of the analysis. Kapferer’s Brand Identity Prism is applied to assess shifts in brand identity and their implications for customer perception. Findings: The findings of this paper shows that, across the three automotive companies, the brands that preserved their kernel traits while repositioning their identity received positive responses from the customers. Moreover, it is shown that the clearer the communication the smoother the repositioning was perceived by the customers. Originality/Value: Prior research examined how the automotive industry is shifting toward electrical vehicles. However, limited research was done about how this shift caused automotive companies to reposition their brands and the effect this has on current customers. This study is examining this gap research.
Keywords: Brand Identity; Positioning; Kernel; Peripheral Values; Jaguar; Kia; BMW; Electric Vehicles.